1954
DOI: 10.1113/jphysiol.1954.sp005215
|View full text |Cite
|
Sign up to set email alerts
|

The equilibrium between carbon monoxide and sheep haemoglobin at very high percentage saturations

Abstract: According to the intermediate compound hypothesis (Adair, 1925)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
2

Year Published

1961
1961
2009
2009

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 14 publications
4
29
2
Order By: Relevance
“…There is at present no satisfactory direct method for studying the oxygen equilibrium curve in this saturation range. However, Roughton (1954) had shown that in this saturation range and at pH 9-1 the oxygen and carbon monoxide equilibrium curves are related, and if L4 is known K4 may be found from the relationship L4 = MK4. M is the value of…”
Section: Equilibrium 8tudiesmentioning
confidence: 95%
See 3 more Smart Citations
“…There is at present no satisfactory direct method for studying the oxygen equilibrium curve in this saturation range. However, Roughton (1954) had shown that in this saturation range and at pH 9-1 the oxygen and carbon monoxide equilibrium curves are related, and if L4 is known K4 may be found from the relationship L4 = MK4. M is the value of…”
Section: Equilibrium 8tudiesmentioning
confidence: 95%
“…Measurements on the carbon monoxide equilibrium in the range 99 0-99.5% saturation at 190 C were made by the method described by Roughton (1954). From two to four determinations were made for each haemoglobin.…”
Section: Equilibrium 8tudiesmentioning
confidence: 99%
See 2 more Smart Citations
“…With haemoglobin solution containing more than 0 5 atm partial pressure of CO, no significant amounts of CO dissociate from chemical combination with the haemoglobin during the 5 min shaking period, but with low partial pressures of CO a correction was necessary for this factor. The recent data of Roughton (1951) on dissociation of carboxyhaemoglobin between 98 and 100% saturation were used for this purpose.…”
Section: Methods I Diffusion Apparatusmentioning
confidence: 99%